GRAFTING OF ACRYLONITRILE ONTO POTATO STARCH (PS) USING eERIC AMMONIUM NITRATE As INITIATOR (Biological Sciences - PJSIR, 2001)
Graft copolymerization of acrylonitrile (AN) onto potato starch (PS) using eerie ammonium nitrate as initiator wasaccomplished. Before grafting starch was gelatinized in two ways; one is dispersing PS in water and other in aqueousbutanol. The results show that PS gelatinized in aqueous iso-butanol facilitates the grafting of growing polymer chain of ANonto backbone slightly better than PS gelatinized in water. The effects of monomer, backbone and catalyst concentration onrate of conversion of monomer, rate of graft copolymerization, rate of homopolymerization, grafting efficiency and graftingrate are discussed in detail. The absorbency of saponified products of each sample was determined in distilled water, tapwater and aqueous solution ofNa Cl and KCl and discussed thoroughly.